Pelatihan Desain Grafis Menggunakan Adobe Photoshop untuk Pembuatan Produk Cetak Kreatif pada Media Hardcase di SMK PAB 8 Sampali Jurusan TKJ - Wirhan Fahrozi; Linda Wahyuni; Hardianto Hardianto; Erwin Ginting; Charles Bronson Harahap (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
The development of digital technology requires vocational high school students to have additional skills relevant to the needs of the creative industry, one of which is graphic design. This community service activity aimed to improve the skills of students at SMK PAB 8 Sampali, Department of Computer and Network Engineering, in creating graphic designs using Adobe Photoshop and applying them to creative printed products on hardcase media, such as wooden clocks, mugs, phone cases, and other merchandise products. The activity was carried out through training, demonstration, hands-on practice, mentoring, and evaluation of participants’ works. The materials included an introduction to basic graphic design concepts, the use of Adobe Photoshop tools, layout arrangement, color selection, text application, image editing, and file preparation for printing or screen-printing processes. The results showed that participants were able to understand the basics of graphic design, use basic Adobe Photoshop features, and produce simple designs that could be applied to hardcase media. This activity also provided students with insight into creative business opportunities in design, digital printing, screen printing, and custom merchandise.